2006
DOI: 10.1051/0004-6361:20053639
|View full text |Cite
|
Sign up to set email alerts
|

Infrared detection of gas phase formaldehyde towards the high mass protostar W33A

Abstract: We report the detection of numerous absorption lines of the ν 1 band of gaseous formaldehyde (H 2 CO) near 3.6 µm towards the high-mass protostar W33A. This is the first infrared detection of gaseous H 2 CO in an interstellar cloud. An upper limit toward RAFGL 7009S is also reported. The column density of H 2 CO detected at 3.6 µm toward W33A is much higher than that measured in large beam millimeter wave observations toward the same source, suggesting that it is concentrated close to the infrared continuum so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Complex radial motions have been observed in this source, but their amplitude is also small (<0.05 km s −1 , . As a result, we are currently unable to distinguish between gas phase and grain surface chemistry for the H 2 CO formation, which has long been enigmatic in a variety of objects (e.g., Roueff et al 2006). Future studies will address this important issue further.…”
Section: Discussionmentioning
confidence: 99%
“…Complex radial motions have been observed in this source, but their amplitude is also small (<0.05 km s −1 , . As a result, we are currently unable to distinguish between gas phase and grain surface chemistry for the H 2 CO formation, which has long been enigmatic in a variety of objects (e.g., Roueff et al 2006). Future studies will address this important issue further.…”
Section: Discussionmentioning
confidence: 99%
“…The Submillimeter Array (SMA) high-resolution observations showed that W33 Main harbors multiple ultra-compact H II regions and three high density clumps (W33 Main-A, W33 Main-B1, W33 Main-B2) embedded in a dense gas envelope detected in C2H (Jiang et al 2015). W33 A has been studied based on the observations in various wavelengths (Gibb et al 2000;Roueff et al 2006;Davies et al 2010;de Wit et al 2007de Wit et al , 2010. Galván-Madrid et al (2010) detected high-velocity gas associated with an outflow in the CO J = 2-1 transition by SMA 230 GHz band observations in W33 A.…”
Section: High-mass Star Forming Region W33mentioning
confidence: 99%
“…[165] Following this idea, amino acids were produced in the laboratory by UV irradiation of interstellar ice analogues composed of H 2 O, CH 3 OH, NH 3 ,a nd HCN; [166] H 2 O, CH 3 OH, NH 3 ,C O, and CO 2 ; [167] and H 2 O, CH 3 OH, and NH 3 . [169] However,s ome of the chemical precursors of amino acids,s uch as glycolaldehyde (HOCH 2 CHO), [170] formamide (HC(O)NH 2 ), [171] and formaldehyde (CH 2 O) [172] have been identified in different objects of the ISM. [169]).…”
Section: Formation Of Precursors To Lifementioning
confidence: 99%
“…No other amino acid has been observed up to now. [169] However,s ome of the chemical precursors of amino acids,s uch as glycolaldehyde (HOCH 2 CHO), [170] formamide (HC(O)NH 2 ), [171] and formaldehyde (CH 2 O) [172] have been identified in different objects of the ISM.…”
Section: Formation Of Precursors To Lifementioning
confidence: 99%